2021
DOI: 10.1038/s41467-021-25792-0
|View full text |Cite
|
Sign up to set email alerts
|

A high-risk retinoblastoma subtype with stemness features, dedifferentiated cone states and neuronal/ganglion cell gene expression

Abstract: Retinoblastoma is the most frequent intraocular malignancy in children, originating from a maturing cone precursor in the developing retina. Little is known on the molecular basis underlying the biological and clinical behavior of this cancer. Here, using multi-omics data, we demonstrate the existence of two retinoblastoma subtypes. Subtype 1, of earlier onset, includes most of the heritable forms. It harbors few genetic alterations other than the initiating RB1 inactivation and corresponds to differentiated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
104
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(145 citation statements)
references
References 112 publications
17
104
2
1
Order By: Relevance
“…Correlation of the clinical and pathological characteristics of the investigated RB tumors with the TFF1 expression status in the AH of the patients' eye did not allow for any stratification. The lack of correlation is most likely attributable to the comparatively small sample size, because we and others have already shown that TFF1 expression in RB tumors indeed correlates with clinical parameters [4,9]. Our group demonstrated that TFF1 correlates with a higher clinical tumor-node-metastasis (TNM) stage and poorly differentiated tumor cells [8] and a recent study showed that TFF1 is linked to RBs which are associated with a higher risk of metastasis, referred to as subtype 2 [4].…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Correlation of the clinical and pathological characteristics of the investigated RB tumors with the TFF1 expression status in the AH of the patients' eye did not allow for any stratification. The lack of correlation is most likely attributable to the comparatively small sample size, because we and others have already shown that TFF1 expression in RB tumors indeed correlates with clinical parameters [4,9]. Our group demonstrated that TFF1 correlates with a higher clinical tumor-node-metastasis (TNM) stage and poorly differentiated tumor cells [8] and a recent study showed that TFF1 is linked to RBs which are associated with a higher risk of metastasis, referred to as subtype 2 [4].…”
Section: Discussionmentioning
confidence: 75%
“…The lack of correlation is most likely attributable to the comparatively small sample size, because we and others have already shown that TFF1 expression in RB tumors indeed correlates with clinical parameters [4,9]. Our group demonstrated that TFF1 correlates with a higher clinical tumor-node-metastasis (TNM) stage and poorly differentiated tumor cells [8] and a recent study showed that TFF1 is linked to RBs which are associated with a higher risk of metastasis, referred to as subtype 2 [4]. Summarizing, one can state that the identification of TFF1 in the AH of RB patients opens the field for new diagnostic approaches.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations